Full circle, but a different world: Reflections on agricultural and rural development in a radically transforming aid and development context - Omamo, Steven Were (Tropical Agriculture Association International, 2025)
You think you understand development until you step into a different role within it. I started my career as a university lecturer in Kenya, moved into international agricultural research, transitioned into food assistance policy, programme development and front-line humanitarian response, spent time inside a grant-making organisation, worked in an international financial institution, briefly entered the private sector, and now lead a global food policy research team and serve as Director for Africa. From these different vantage points, I have watched the aid and development landscape shift both incrementally and fundamentally. The ‘development world’ I entered 35 years ago was nothing like that of today. The current funding landscape is leaner, faster and far more impatient. Where donors once spoke of long-term transformation, they now focus on short-term returns. Where development once aimed to build broadbased capacity over the longer term, it now targets more immediate, short- to medium-term measurable outputs. Meanwhile, the major global challenges demanding solutions – climate change, economic volatility and conflict – imply the need for resources, analysis and operational capacity at levels never before mobilised. Importantly – and this is a major theme for me – in the face of these pressures, adaptation and innovation have emerged in ways that were unimaginable just a decade ago. We now see growing roles for local organisations and much support for ‘localisation’ in aid and development, and increased emphasis on the roles of private enterprises and digital technologies in opening new ways to tackle difficult challenges. The associated shift in power and influence away from international actors to national and local actors has been real. This represents an important opportunity, if correctly understood and seized.